حقوق الطفل اليمني – إشكاليات الواقع وتطلعات المستقبل - لينا محمد أحمد العبسي (مجلة الدراسات الاجتماعية, 2016)
Legal protection is one of the most important protection means, especially for the most vulnerable groups in the society including children. For this reason, the government of Yemen has signed and ratified a number of related Arab, regional and global conventions and enacted a number of national laws and legislations in line with childhood situation in Yemen. Despite these efforts, children still suffer a tragic situation due to several reasons including the legal deficiencies which limit its role of law in protecting childhood. This study aimed at investigating the legislative efforts of the Republic of Yemen and the legal problems regarding children in Yemen. The study adopted the analytical approach in surveying Arab, regional and international documents, laws and conventions, as well as analyzing the content of some of the Yemeni laws and legislations in a sociological perspective. The study results revealed that laws and legislations are important means to ensure and maintain children rights. Yemen exerts great efforts in the legal field though these efforts remain below the required level, and the legal side suffers from real problems that diminish its importance and weaken its role and social status. The study proposed implementing the legal and legislative plans, programs, measures and procedures regarding children, enacting more laws that convict child abuse, exploit or violate his rights, and referring all the issues related to child abuse, exploitation or violation to justice.